State and Social Solidarity Economy: Friends or foes? The potential for co-construction of public policies for Social Solidarity Economy in Greece - Adam, Sofia; Kavoulakos, Karolos Iosif (The Greek Review of Social Research, 2020)
This paper focuses on the relations between state and Social Solidarity Economy (SSE) practices regarding the case of Law 4430/2016 on Social and Solidarity Economy actors in Greece. This legal framework was introduced at a time when a new wave of cooperativism had already emerged in crisis-ridden Greece and a party of the radical left with strong affiliations with social movements was elected to power. In this context, it is interesting to explore the potential for a new trajectory in state and SSE interactions through the analytical perspective of the co-construction of public policies. The results presented in this paper are based on a research project funded by the Heinrich Boell Foundation Thessaloniki Office. The research design is based on mixed methods: a content analysis of the contributions implemented by relevant stakeholders during informal and formal consultation processes and the analysis of data from semi-structured interviews with selected networks and support organizations for SSE in Greece.